New records of Nevrorthus apatelios H. Aspöck, U. Aspöck and Hölzel, 1977 (Neuroptera: Nevrorthidae) from Bosnia and Herzegovina - Susanne Randolf; Stefan Andjus; Bojana Tubić; Harald Bruckner; Michaela Brojer; Maja Zagmajster (Natura Sloveniae)
During the »Neretva Science Week« in summer 2022, two larvae of Nevrorthus apatelios were found in Eastern Bosnia and Herzegovina. These are the first confirmations of the species in the country since a single observation of one adult from Sarajevo almost 100 years ago. New records come from two sites of the upper course of the Neretva River, near Ulog village: one larva was found in a benthic fauna sample collected at the river bottom near Rastovac, while the second was pumped from the river interstitial at depths 30-60 cm, in the area near Cerova. Based on these findings we provide a description of the larva. Nevrorthus apatelios lives in highly oxygenated waters, and is a good indicator of clean waters. We discuss the potential reasons for rare observations of the species in the country, and conservation implications in light of ongoing environmental pressures in the currently pristine part of the upper course of Neretva River.